A prototype low-carbon segmented concrete shell building floor system. (March 2023) - Oval, Robin; Nuh, Mishael; Costa, Eduardo; Madyan, Omar Abo; Orr, John; Shepherd, Paul
Abstract: Concrete shell structures offer a mechanically efficient solution as a building floor system to reduce the environmental impact of our buildings. Although the curved geometry of shells can be an obstacle to their fabrication and implementation, digital fabrication and affordable robotics provide a means for the automation of their construction in a sustainable manner at an industrial scale. The applicability of such structures is demonstrated in this paper with the realisation of a large-scale concrete shell floor system, completed by columns, tie rods, and a levelled floor. The shell was prefabricated off-site in segments that can be transported and assembled on-site, and which can be disassembled to enable a circular economy of construction. This paper presents the conceptual and structural design; the automation of fabrication, thanks to an actuated, reconfigurable, reusable mould and a robotic concrete spraying process; the strategy and sequence of assembly and disassembly on-site using standard scaffold elements; and the sustainability assessment using life-cycle analysis. This prototype offers a reduction of about 50% of cradle-to-gate embodied carbon benchmarked against regular flat slabs before further improvement and optimisation.